The Effectiveness of Wordwall Game-Based Learning Media on Student Learning Outcomes of Simple Past Tenses - Maslahat, Siti; Alawiyah, Anisa; Sugara, Ria Dewi Hudayani (JEdu: Journal of English Education, 2024)
The research is The Effectiveness of Wordwall Game-based Learning Media on Student Learning Outcomes on Simple Past Tense. This research was conducted in class IX MTs Al-Hibsiyah Lengkong. The objectives of this study are (1) To determine whether there is an effect of using Wordwall game-based learning media on student learning outcomes of simple past tense material, and (2) To determine the effectiveness of using Wordwall game-based learning media as seen from student responses. This research uses a pre-experimental method, with a One Group Pre-test - posttest design consisting of six meetings including treatment. Sampling using purposive sampling technique, with a total sample of 20 ninth-grade students. Data was obtained based on test instruments (pre-test - post-test) and questionnaires. The results showed that the post-test results were greater than the pre-test results, which means that students experienced an increase in simple past-tense learning outcomes after using Wordwall game-based learning media. The average pre-test score obtained by students is 54.75 and the post-test is 80.75 and the acquisition of the overall N-Gain average value is 58,64%, therefore students' scores have increased significantly. The average questionnaire result value is 88.50%, including the Strongly Agree category, which means that the use of the Wordwall game is very effective to be used as a learning media for students simple past tense. This is also evidenced by the results of hypothesis testing using Paired Sample t-test through SPSS 22, that the value of Asymp. Sig. (2-tailed) 0.000 < 0.05, it can be concluded that the hypothesis is accepted.Keyword: Wordwall Game-based Learning Media, Learning Outcomes, Simple Past Tense